Polski stres, fińska wolność ... : Polish stress, Finnish freedom ... - Lipiec Stanisław (Wydawnictwo Naukowe Wyższej Szkoły Biznesu i Nauk o Zdrowiu, 2016)
For long time we have asked why Polish school is worse than plenty of the Western world school systems. Teaching programs, schooling organisation, pedagogues preparation or cultural cornerstones of tutoring and teaching are emphasised. Very often everybody contends that Finnish school system is one of the best in the world. The author of this article tries to proof that differences are not so big. The greatest factor distinguishes Polish from Scandinavian approach to students is the lack of school stress. We observe an absence of both the daily and organisational stress of students and teachers. Researches were made in Finnish school during the author's job at schools in Northern Finland. Researches were led from September 2013 until June 2014 on the probe of 450 students and 51 teachers. Investigations were made by the quality methods like observation, participant observation, depth interview and structured interview. The author describes also the individual approach of teachers to students, which do not ... : Od dawna zadajemy sobie pytanie, dlaczego polska szkoła jest gorsza niż wiele innych systemów szkolnych świata zachodniego. Podkreśla się, że problemem są: programy nauczania, organizacja szkolnictwa, przygotowanie edukacyjne pedagogów i kulturowe podstawy nauczania i wychowania. Równolegle często mówi się, że fiński system szkolnictwa jest jednym z najlepszych na świecie. Staramy się udowodnić, że różnice pomiędzy polskim i fińskim systemem szkolnictwa nie są aż tak duże. Największym czynnikiem odróżniającym polskie podejście do ucznia od nordyckiego jest brak stresu szkolnego. Obserwujemy pośród uczniów i nauczycieli brak stresu zarówno codziennego, jak i systemowego. Badania zostały przeprowadzone w fińskim zespole szkół podczas pracy autora w szkołach północnej Finlandii. Badania prowadzono od września 2013 r. do czerwca 2014 roku na próbie 450 uczniów i 51 nauczycieli. Badania prowadzono za pomocą metod jakościowych, takich jak obserwacja, obserwacja uczestnicząca, wywiad pogłębiony i wywiad ...